Intention to Overcome Dating Violence Junior High School X in Urban Area The City of Semarang - Rahma, Nis Syifa'ur; Aprianti (Health Science UDINUS, 2023)
The Women’s Empowerment and Child Protection of Indonesia in 2022 showed the highest number of violence cases based on education level in Junior High School with 5,945 cases. This study analyzed the intention to overcome dating violence in adolescents at Junior High School X in the urban area of Semarang City. This research is a quantitative study with a cross-sectional design. The population of this study amounted to 484 populations using a purposive sampling technique with a sample of 114 respondents. The data was collected by a self-administered questionnaire and the data was analyzed using a chisquare test. The results showed that perceived vulnerability (64%), perceived seriousness (59.6%), response efficacy (61.4%), self-efficacy (70.2%), and intention (93%) were categorized as high in overcoming violence in a relationship. However, there is no significant relationship between perceived vulnerability (p-value=0.255), perceived seriousness (p-value=0.712), selfefficacy (p-value=0.05), and response efficacy (p-value=0.257) with the intention of overcoming dating violence. The recommendation is to provide education to students about the risks of dating violence.